The perspective of Speech and Language Pathologist about Outcomes of an Early Language Delay in Children Less than 5 Years Old - Shafique, Sibgha; Tahira, Sadia; Ahmed, Muhammad; Yaqoob, Saba; Maqsood, Hiba; Zulfiqar, Nimra (International Journal of Rehabilitation and Special Education (IJRSE), 2022)
Background: Language is the systematic and standard use of sounds (or signs or written symbols) for communication or expression purpose. In humans language is controlled primarily by the left cerebral hemisphere, and the right hemisphere is specialized for processing visual-spatial information. This actually depends on the handedness of humans. It is evaluated that around 95% of right-handers and 70% of left-handers appear left-hemisphere dominant for language. Early language delay is a condition that called a common developmental disorder. Persistent delay may lead to adverse impacts on the emotional, behavioral and social abilities of children. Objective: The objective of the present study was to find out the perspective of speech and language pathologists/therapists about the outcomes of an early language delay in children less than 5 years old. Materials & Methods: This descriptive study was carried out at NUR International University, from 1st March 2021 to 30 September 2021 to determine the outcomes of an early language delay in less than 5 years old. For this purpose data was collected from almost 50 speech therapist working with the language delaychildrensthrough self-designed questionnaire. Questionnaire which was used as data collecting instrument that was designed by expert opinion and literature review. Results: Results show that the most facing outcomes are difficulty in understanding verbal communication 30(60%), turn-taking during conversation as well as playing 32(64%), focus and concentration difficulties 28(56%), difficulty in linguists use 30(60%), difficulty in imitation 25(50%), performing cognitive tasks30(60%), academic issues 30(60%), arranging syntactic and semantics 25(50%), non-compliance 29(58%), emotional tantrums 35(70%) and physical aggression on siblings and animals 31(62%). Conclusion: The children are facing difficulties in their academic life and extremely confront the behavioral, social and, emotional problems in their daily life.